Analisis Perbandingan Sistem Budidaya terhadap Karakteristik Sel dan Performa Pertumbuhan Rumput Laut (Gracilaria verrucosa) - Prayundika, Hanifah Zahra; Rahim, Andi Rahmad (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Gracilaria verrucosa has an important role in the agar industry sector and is a major contributor to food security, so cultivation techniques are needed to increase seaweed productivity. This study aims to compare the Gracilaria verrucosa seaweed cultivation system on cell characteristics and seaweed growth performance. This study is a quantitative study with an experimental method. The technique for determining seaweed cell characteristics uses plant histology methods including fixation, filtration, and staining of specimens to see the cell structure under an optical microscope, while to measure seaweed growth performance using absolute length, specific growth rate (SGR), and number of thallus. Data analysis uses t-test inferential statistics. The results showed that (1) the extensive system produced better growth performance, with absolute length (9.7 ± 1.4 cm), SGR (28.6%), and higher number of thallus (256.6 ± 16.8); (2) cell characteristics in the extensive system produced larger and more regular sizes, with a higher number of cells at the end of maintenance; (3) there was no significant difference in agar yield between the two systems.